INNV-33. FUNCTIONAL EX VIVO TESTING PROSPECTIVELY IDENTIFIES NEWLY DIAGNOSED GLIOBLASTOMA PATIENTS SENSITIVE TO TEMOZOLOMIDE TREATMENT IRRESPECTIVE OF MGMT METHYLATION STATUS. (14th November 2022) - DesRochers, Tessa; Lipinski, Lindsay; Abad, Ajay; Fenstermaker, Robert; Fabiano, Andrew; Edenfield, Jeffery; Kanos, Charles; Redjal, Navid; Rodriguez, Analiz; Mansouri, Alireza; Zacharia, Brad; Butowski, Nicholas; et al.
Abstract: Standard of care (SOC) therapy for newly diagnosed (ND) glioblastoma (GBM) patients consist of temozolomide (TMZ) concurrent with radiation therapy. It is well known that patients with an unmethylated MGMT promoter are less likely to respond to TMZ, however, this trend is not universal. We have previously shown that 3D Predict™ glioma can identify patient response to TMZ, often differentially than the methylation status would predict. Here we present expanded clinical data relating to functional ex vivo testing capable of identifying patients responsive to alkylating therapies such as TMZ, regardless of methylation status. METHODS: Fresh tissue specimens taken from ND GBM patients enrolled into the 3D PREDICT clinical study were examined by 3D Predict glioma to evaluate ex vivo therapeutic response to TMZ. Overall Survival (OS) and Progression Free Survival (PFS) in patients having â‰¥ 6 months follow-up post-surgery or < 6 months follow up but experiencing progression/death as of September 1, 2022 will be presented. Prospective correlation of clinical response and test-predicted response will be demonstrated in this expanded cohort of ND GBM patients. IMPACT: This data has the potential to change treatment for ND GBM patients by stratifying according to functional therapeutic response rather than epigenetic factors that are not completely predictive of clinical response. It is feasible that 3D Predict glioma could dramatically impact patient care by determining which unmethylated patients should be treated with TMZ, and methylated patients who would potentially derive greater benefit from clinical trials or other treatment regimens.